Adolescents' Attitudes toward Ecstasy Using - N Seyedfatemi; F Khoshnavaye Foomani; N Behbahani; F Hoseini (Tehran University of Medical Sciences, 2008)
Background & Aim: Using illicit drugs such as Ecstasy is a deviant behavior in adolescents. Attitude toward using illicit drugs can predict its usage. This study was carried out in order to determine the adolescents' attitude toward using Ecstasy in 2006. Methods & Materials: In this cross-sectional study, eight hundred adolescents aged 16-18 years who lived in the west of Tehran recruited from public regions of municipality. Data was gathered using authors-structured questionnaire. After filling in informed consents, the questionnaires were completed by the respondents. Results: Findings revealed that 78.9 % of the adolescents had negative attitudes and 17.5% had positive attitudes toward using Ecstasy. Boys and girls attitudes were not significantly different. Conclusion: Regarding relatively high negative attitudes among the adolescents toward Ecstasy using, it seems that investments in health promoting programs were appropriate. Nevertheless, along with these programs, parents and teachers should pay more attention to the issue.   Key words: adolescent, attitude, drug abuse, Ecstasy